An experimental study on out-of-plane inelastic buckling strength of fixed steel arches. (1st September 2015) - Guo, Yan-Lin; Zhao, Si-Yuan; Pi, Yong-Lin; Bradford, Mark Andrew; Dou, Chao
Highlights: Experiments on out-of-plane inelastic buckling of fixed arches are carried out. FE numerical models of fixed arches are validated by experimental results. Design equations for out-of-plane strength of fixed arches are validated by tests. Abstract: This paper presents an experimental study on the out-of-plane inelastic buckling strength of fixed circular steel arches under symmetric and non-symmetric loading. A test loading arrangement that allows for lateral deflections to develop freely under vertical loading is described. A finite element (FE) model consisting of the tested steel arch and the loading system is established for carrying out supplementary numerical investigation on the inelastic out-of-plane buckling strength of the fixed steel arches. The FE numerical model is validated by the experimental results. From the experimental results and supplementary FE investigation, it is found that the out-of-plane inelastic buckling strength of fixed steel arches is influenced significantly by the magnitude and distribution of initial out-of-plane geometric imperfections, as well as the out-of-plane elastic buckling modes and the in-plane loading patterns. It is also found that the out-of-plane buckling strength of a fixed steel arch under non-symmetric loading is lower than that under symmetric loading. Based on the experimental and FE results, a lower bound interaction equation is developed for predicting the out-of-plane inelastic buckling strength in the design of fixed circular steel arches against their out-of-plane failure.